The comprehensive study of product criteria on infant-wrap (InfaWrap) device: engineering perspective - Mohd Hanafi, Abdul Rahim; Mohd Azrul Hisham, Mohd Adib; Nur Hazreen, Mohd Hasni (IOP Publishing, 2020)
Nowadays, most of the parents still monitor their baby’s health using a manual oximeter device. However, the existing oximeter device was a hassle for infant and presented the monitoring process difficult. In this paper, two different prototype of the infant-wrap (InfaWrap) device is well compared. This InfaWrap device is purposely to monitor the SpO2 and heart rate of the baby. The device also easier to use, fast and provides accurate on baby’s SpO2 and heart rate. Presently, the main problem was related to the clinical which used of the conventional wrapping concept. Normally, the method involved the movement of the infant's leg which is easier to deprive. This study focuses on the perspective of engineering students on InfaWrap device criteria needed from the customer compare between prototype 1 and prototype 2. The results obtained in the perspective study generally shows the prototype 2 is better than the prototype 1 especially on design, safety, comfortability, size, and weight. Finally, by use of this comprehensive study of the product criteria on InfaWrap device, we expected to help experienced professional’s designers to develop more good products in the future especially on medical devices.